2016
DOI: 10.1007/s00266-016-0760-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Rhinoplasty Maneuvers on Upper Lip Position and Incisor Show

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…This muscle is contracted repeatedly daily due to laughs and talking and may increase the nasal length over time. 15 In a retrospective study Pi et al (2017) concluded that the placement of columella strut and extended spreader graft and the DSN muscle transection resulted in downward movement of the upper lip and lower maxillary anterior incisors show during smile. 5 It was concluded in the present study that these measures increase the upper lip length and protrusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This muscle is contracted repeatedly daily due to laughs and talking and may increase the nasal length over time. 15 In a retrospective study Pi et al (2017) concluded that the placement of columella strut and extended spreader graft and the DSN muscle transection resulted in downward movement of the upper lip and lower maxillary anterior incisors show during smile. 5 It was concluded in the present study that these measures increase the upper lip length and protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a retrospective study Pi et al (2017) concluded that the placement of columella strut and extended spreader graft and the DSN muscle transection resulted in downward movement of the upper lip and lower maxillary anterior incisors show during smile. 5 It was concluded in the present study that these measures increase the upper lip length and protrusion. The present study also investigated the vertical movement of the upper lip and found lower elevation for upper lip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After addressing a visible facial deformity in rhinoplasty, patients may become aware of subtle smile abnormality. [3] In this study, we compared the outcomes of lip and smile position in rhinoplasty candidates undergoing TIG with or without SEG.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The rhinoplasty was done in patients under general anesthesia. The incisions were highlighted using methylene blue (Hamilton and Grant, 2014;Pi et al 2016). For dome splitting, no other techniques such as alar contour graft and alar base resection applied.…”
Section: Dome Splitting Surgical Proceduresmentioning
confidence: 99%